An examination of Aristotelian modality - Munshi, Salma (Rhodes University, Faculty of Humanities, Department of Philosophy, 1986)
From introduction: A popular misconception regarding Aristotle's views on modality is that Aristotle adhered to the doctrine of no unrealized possibilities. According to this doctrine, all possibilities are realized in time; in other words, if it is possible that something could happen, then at some time it is the case that that happens. For example, if it is possible for Socrates to escape from prison, then there will be a time at which Socrates will actually escape from prison. On this view, the possible and the actual co-incide; whereas there is abundant evidence that Aristotle was careful to maintain a distinction between the possible and the actual.
Keywords: Aristotle; Modality (Theory of knowledge)